STRUKTUR JARINGAN INTERKONEKSI, TAHAPAN PEMBANGUNAN E-GOVT DAN FAKTOR YANG MEMPENGARUHI PENERAPAN STRUKTUR JARINGAN INTERKONEKSI (Survai Tentang Interkoneksi di kalangan Aparatur Instansi pelayanan publik bidang informasi dan dokumentasi) - Ari Cahyo Nugroho (Jurnal Studi Komunikasi dan Media, 2016)
This study first asks questions about the implementation of the interconnection network structure in the public service agencies in the field of information and documentation. Both questioned the influence of the quality of the development stages of e-govt on the quality of the implementation of the interconnection network structure and the third about the other factors that affect the implementation of the interconnection network structure among public service agencies. The findings showed problems related to the first and based on respondents' awareness of Interconnection Network structure adopted in the institution where they work, their agencies were divided into three categories Interconnection Network Structure, LAN; MAN; and WAN. However Interconnection Network Structure category more dominant LAN adopted in Bengkulu and Jambi. In the province of Bangka Belitung dominant Interconnection Network Structure category MAN. While the agency adopters of internet network structure and network without wires is not found none. Related to the second problem, the agency they were divided into four categories, namely: Preparation; Maturation; Consolidation and Utilization. Stages of E-government level appears most prominent Preparations have been done in three research sites. While the agency has reached the stage of utilization, not many. The number of establishments that have reached the stage of utilization exist in Bengkulu and the province of Bangka Belitung. Statistical test results one tail bivariate with SPSS 17.0 by size Pearson association, shows that the relationship among variables "Quality development phases of e-govt" and variable "quality of implementation of the interconnection network structure" significant at alpha 0.01, respectively. The third related issue, theoretically the factors in the form factor of the culture apparatus sharring attitude and culture of documentation and availability of IT human resources quality factor. Based on the results of one tail bivariate statistical tests with SPSS 17.0 by size association Pearson, variables Culture Sharing (.106 *); quality of human resources (-.343 **) and the quality of infrastructure (-.136 *) significantly affect the application of the categorical variable interconnection network structure in the environment agency. In the development of e-govt should immediately undertake efforts base on empowerment Instruction No. 3/2003-regional apparatus to apparatus. For future similar research should be in the process need to enter the variables that interfere extranous Kultur variable relationship documentation with the application of a categorical variable interconnection network structure. It also needs to include variables "budget" IT satker as independent variables in order to see the correlation with the application of categorical variables interconnected network structure.